ETYMOLOGICAL BACKGROUND OF INTERNATIONAL VOCABULARY IN ENGLISH - Ruziev Khusniddin Bakhritdinovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article explores the origins of international vocabulary in English, focusing on borrowings from Latin, French, and Greek. It outlines key historical stages of lexical borrowing and explains major phonetic adaptations in English. The study shows how foreign words are adjusted to fit the English sound system.